PENELUSURAN SEJARAH AL-QUR’AN VERSI ORIENTALIS: SEBUAH GAMBARAN METODOLOGIS - Ahmad Shams Madyan (IAIN Kediri, 2015)
Although being defined as a scholarly knowledge of Eastern cultures and languages, Orientalism seemed to be confined to a mere discussion on Islam. Orientalist’s hostorical approaches toward the Qur’an have raised heated debates among Muslims. As an approach, Orientalism is not a free value, rather it containes ideology-based accounts despite of its alledgedly scientific nature. This paper attempts to answer whether or not Orientalism’s historical method of interpreting the Qur’an is really scientific or it needs to be countered and criticized.Keywords: Orientalisme, al-Qur’an, Autentisitas